Tuning-in to Clients: The Use of Semiotics in Counselling - Thomas Mark Edwards (Psychotherapy and Counselling Journal of Australia)
Semiotics is about signs, but more so about meaning-making. It therefore has immediate relevance to counselling. The current paper not only seeks to introduce semiotics to counsellors but also to offer skills and methods to enhance the ways in which practitioners see, hear, and understand their clients via the use of signs. In particular, five semiotic practices will be discussed: (1) the clinical relevance of categorising client signs; (2) the value of exploring the connotic meanings of client signs; (3) the effective use of a paradigmatic analysis to uncover hidden meanings; (4) the value of metaphor and irony to therapeutic conversations; and, (5) the necessity of understanding a client’s language code to avoid erroneous clinical judgements. Finally, in adopting the use of semiotics, practitioners are able to reconsider their practice by looking beyond client symptoms to engage meaningfully with entire sign systems, which confer additional and important clinical information.